Organising general practice for care homes: a multi-method study - Barbara Hanratty; Rachel Stocker; David Sinclair; Katie Brittain; Karen Spilsbury; Daniel Stow; Louise Robinson; Fiona E Matthews (Health and Social Care Delivery Research)
Background General practice provides first-line National Health Service care for around 400,000 care home residents. Good primary care can enhance residents’ health and well-being and optimise use of hospital services. Objectives This study aimed to explore the relationships between organisation of general practice and the perspectives and experiences of residents, general practice and care home staff, outcomes and costs. Design Survey of general practices (2018), qualitative study (2019), analysis of primary care data (2019–21). Policy context National Health Service England Vanguard funded innovation in services for care homes in five areas (2015–8); Enhanced Health in Care Homes introduces standardised care home healthcare processes in England (2020–4). Setting England: national survey; qualitative work in three areas (two Vanguards); analysis of national primary care data across early implementation of Enhanced Health in Care Homes and the COVID-19 pandemic. Participants One hundred and fifty general practice survey respondents; 101 interviewees (general practitioners, practice managers, receptionists, care home managers, nurses, senior carers, residents, relatives, commissioners) in three areas; 103,732 care home residents ≥ 75 years, registered with participating practices in Clinical Research Datalink Aurum 2019–21. Results Qualitative analysis identified three themes concerned with general practitioner services to care homes: relational processes, communication and organisation. Continuity of care, sensitivity to the skills of care home staff and routines of the home, along with a willingness to dedicate time to patients, are all crucial. Different structures (e.g. scheduled visits) provide opportunities to develop effective, efficient care, but flounder without established, trusting relationships. The way in which new initiatives are implemented is crucial to acceptance and ultimate success: telemedicine was an example that generated efficiencies for the National Health Service, but could be a burden to care homes, resented by staff and perceived as a barrier to overcome. One hundred and fifty practices responded to our survey, a majority staffed by ≤ 5 general practitioners. Larger practices were more likely to have a nominated general practitioner for care homes and make weekly scheduled visits. Analysis of primary care data found that in practices with a higher number of care home residents, patients had more contacts with primary care and fewer urgent referrals. Between 2019 and 2021, total contacts and estimated costs increased, and urgent referrals and polypharmacy fell. Limitations Sparse evidence of systematic change in Vanguard areas limited our conclusions about specific initiatives. Implementation of national policy during the COVID-19 pandemic complicates data interpretation. Conclusions Larger practices or those with higher numbers of care home residents were more likely to adopt ways of working that are associated with higher-quality care. However, trusting relationships between care homes and a motivated, adequately resourced primary care workforce may be more important than models of care, in enhancing primary care for care homes. General practices and care homes find creative ways around initiatives that are not perceived to offer any benefits, emphasising the need for local flexibility when implementing national initiatives. Future work Future work could address how best to promote ways of working that prioritise trusting relationships; the absence of care pathways specific to care home patients, and the impact of Enhanced Health in Care Homes on system-wide costs. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 14/196/05) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 11. See the NIHR Funding and Awards website for further award information. Plain language summary Most people who live in care homes are older adults. General practitioners look after their day-to-day medical care, working with care home or community nurses. In England, there have been moves to improve health care for people in care homes. In this study, we looked at how general practitioner services could be delivered to get the best care for care homes. We surveyed practices, interviewed more than 100 people in three different areas of England (pre-COVID) and analysed information from electronic healthcare records in primary care using a large research database. Our qualitative study identified three areas that general practices working with care homes should focus on. These were relationships, the way care is structured, and how changes are introduced. All three need to be in place, to improve experiences and care for care home staff and residents. One hundred and fifty practices replied to our survey – around half made planned visits to care homes, and nominated one person for this work. Bigger practices were more likely to work in ways that should provide good-quality care for care homes. Our analysis of healthcare records (2019–21) showed residents in practices with larger numbers of care home residents saw their general practitioners more often and had fewer urgent referrals. Over the time that policy changes were first introduced in England, residents had more contact with practices, prescribing improved, urgent referrals fell and estimated costs went up. This study provides support for changes being introduced by national policy but emphasises the need for trusting relationships between primary care and care home staff. Future challenges include developing and retaining a skilled primary care workforce that wants to work with care homes. Care pathways to guide general practitioners and care homes when a resident is ill may also be helpful, along with more in-depth analysis of the cost implications. Scientific summary Background General practice provides the point of first medical contact within the healthcare system for residents of UK care homes. Good primary care may enhance residents’ health and well-being and optimise use of hospital services. Yet there has long been a widely held view that care home residents do not receive high-quality primary care. Care homes are challenging settings in which to implement the vision of dignified, person-centred care outlined in government policy. General practitioners (GPs) are tasked with working in partnership with residents, helping them to find their voice, while working more efficiently, and integrating with other community and secondary care services. There has been great heterogeneity in the organisation of general practice services for care homes, both in the number of practices providing services to an individual care home, and in nature, frequency and regularity of primary care contacts with a particular home. NHS England funded the Vanguard initiative (2015–8) to identify and support innovative ways of working with care homes in five areas. This was followed by the introduction of a new policy [Enhanced Health in Care Homes (EHCH), implemented 2020–4] to standardise aspects of health care for residents. This report will address the question of how the organisation of GP services impacts on care home residents’ and staff experiences and examine selected aspects of care over time as the new policy is first introduced. The overall aim is to identify effective ways of serving this important group of patients. Objectives The aim was to identify effective ways of organising general practice for care homes and understand the experiences of residents, general practice and care home staff. Research questions In what ways is the organisation of general practice for care homes associated with better resident outcomes and experiences? What are the implications of different models of GP involvement for residents’ service use and costs? What are the perspectives of residents, relatives and staff in general practices, commissioning organisations and in care homes, on different ways of organising primary medical services for care homes? Which are acceptable and associated with positive experiences for staff, residents and relatives? Methods Methods: survey of general practices working with care homes A fixed-response e-mail survey was designed for completion by practice managers, administrative staff or GPs in England. The survey collected data on practice and care home characteristics, GP staff visits to care homes, and ways of working. Seven items were closely aligned with the organisational changes that occurred in the areas where NHS England Vanguard care home initiatives were introduced. Information about the survey was distributed to Clinical Commissioning Groups (CCGs) who circulated to practice managers by e-mail. Individuals who were interested in participating were sent an information sheet and consent form, followed by an electronic copy of the study questionnaire. The data were aggregated and analysed using frequencies and percentages. Hierarchical clustering analysis was used to classify practices into groups based on their responses. Methods: qualitative study Interviews were conducted with GPs, practice managers and receptionists, care home managers, nurses, senior carers, residents, relatives and service commissioners. Interviews explored perceptions of the different models of general practice care, positive and negative consequences of different ways of working, how different models of care influence staff experiences, job satisfaction and resident and family experiences, and the underlying structures, processes and values that perpetuate these models. Fieldwork was conducted in three contrasting areas of England. Two had recently implemented new models of GP care for care homes, and the other had had no recent innovation. We used information collected in the survey to target care homes of a variety of types (residential/nursing/mixed), area-level social disadvantage and local GP practice size. Commissioners were recruited via existing links with the research team, public CCG/local authority staff lists and snowball sampling (where participants suggest another potential participant working in a similar commissioning role). The interviews were audio-recorded, transcribed and analysed using a thematic approach. Line-by-line coding generated an initial thematic framework that was refined as data collection progressed. The finalised framework was then placed into a wider structure of context, organisation, individual and system to ensure consistency of coding and agreement/refinement of themes. Our approach was both iterative and inductive; we interrogated the data to answer our research questions and also identified new themes. QSR international NVivo 11 (Warrington, UK) software was used to manage the data. Methods: quantitative study We analysed data from Clinical Research Datalink Aurum, which contains longitudinal primary care records of 14.8 million individual patients. Residents aged 75 years + who contributed person-time for all or part of 2019 or 2021 were included. Data on contacts, referrals and prescribing were extracted. Analyses were completed using R version 4.2.2 (The R Foundation for Statistical Computing, Vienna, Austria) and IBM SPSS 29.0.0.0 (241) (IBM Corporation, Armonk, NY, USA). Public and patient involvement We recruited a patient and public involvement (PPI) group from our larger Newcastle University supported Care Home Interest Group (see Report Supplementary Material 1). The intention was to seek views on study design, procedures, analysis and dissemination. Attendees were from a range of backgrounds. Some had no direct experience of this sector. Others were current or former care home staff, local authority, NHS or third-sector employees. The group met twice per year, with an average attendance of eight (plus the study team). We used role-play and actors to engage the PPI group in the data analysis. Findings Our survey showed that general practices with larger staff numbers and patient list sizes were more likely to adopt working practices thought to be associated with higher-quality care. These included the provision of scheduled visits, taking part in multidisciplinary team meetings and facilitating specialist nurse input into care homes. Analysis of primary care data from 103,732 care home residents produced complementary findings. Care home patients of practices with higher numbers of residents had more contacts with general practice staff and were less likely to have high numbers of emergency referrals. Between 2019 and 2021, the total number of residents fell, and there were fewer practices with a high number of registered care home patients. Total contacts and monthly contacts were higher in 2021, which may reflect more intensive end-of-life care, associated with a higher death rate during the COVID-19 pandemic. Compared to 2019, the proportion of residents who were referred urgently was lower, but levels of ‘2-week wait’ referrals were similar. The proportion of residents without polypharmacy was higher in 2021 than 2019, and the proportion with excessive polypharmacy was also lower. Applying standardised costs to our data suggests that increasing contacts over time may increase primary care costs by up to £35,000 per annum for an average care home. This increased expenditure is unlikely to be offset by improvements in prescribing or referral practices. This issue merits more detailed scrutiny, with consideration of hospital admissions and individual drug costs to produce an accurate system-wide picture. We identified three main themes in our qualitative study, relating to general practice services to care homes – relational processes, communication and organisation. The interaction between these three was critical to enhancing care. Trusting relationships are at the heart of effective general practice for care homes. Our findings suggest that continuity of care, sensitivity to the skills and expertise of care home staff and a willingness to dedicate time to patients were crucial. Different structures provided opportunities to develop effective, efficient care, but could flounder if relationships were not established. The potential of the ward round model, for example, was realised only when relationships were constructive. The way in which innovation is introduced is crucial to acceptance and ultimate success. Telemedicine was an example of a new way of working that generated efficiencies for the NHS but could be a burden to care homes, resented by staff and perceived as a barrier to overcome. The ingenuity of general practice and care home staff to circumvent initiatives that offered no perceived benefits to themselves, or care home residents, was evident, and emphasised the need for local flexibility when implementing national policies and to support grass roots innovation. Implications for health care Recognise the importance of relationships Our findings suggest that good care and outcomes for care home residents will lie in models of care that enable effective working relationships to thrive. This finding adds to the body of evidence that emphasises the importance of human factors in service improvement and development. It suggests that an emphasis on reorganisation and innovation may be insufficient on its own. The challenge for service commissioners and providers will be finding the resources (particularly time) to foster constructive relationships across organisations. Training of health professionals The importance of relationships and respect for staff expertise point to a need to develop primary care expertise and interest in care home health. Developing a motivated healthcare workforce for care homes, skilled in caring for older adults with multiple long-term conditions and frailty, should be a priority. Primary care networks and integrated care systems Continuity of care from primary care professionals allows relationships to develop. Our findings suggest that designating individuals for specific care homes and allowing protected time is helpful. We also know that size of practice is also associated with other ways of working that may produce better quality of care. A critical mass of personnel is key to facilitate specialisation and allow allocation of staff to specific activities of interest, such as care home visits and multidisciplinary team meetings. Structural changes in the NHS, such as the establishment of primary care networks, may be helpful in ensuring that appropriately skilled primary care staff are available across all areas. Scheduled visits for care homes Scheduling regular visits is widely perceived as a way of enhancing the quality of health care for care homes. This study suggests that this intervention has potential to introduce efficiencies into care delivery and it is generally well received by homes. Implementation of change Our findings support a considered approach to implementation of new initiatives. Ongoing evaluation of the process of embedding an intervention into practice is essential, including scrutiny of the intended and unintended consequences. Telemedicine, for example, may reduce the need for GPs to visit care homes, particularly out of hours. However, it can increase care home staff workload, if they are drawn away from their usual duties. Multidisciplinary working This study suggests a lack of awareness within care homes of the potential benefits of pharmacist input. However, it is also possible that our interviewees’ narratives reflected care homes’ lack of influence on the location and actions of NHS pharmacy staff. Recommendations for research Research into promotion of relational practice between care homes and primary care Promotion of ways of working that prioritise helpful relationships in health and social care (relational practice) has potential to enhance outcomes for care home residents. Previous work has established the importance of an atmosphere of respect and trust, a purposeful focus on relationships; and a physical environment that supports nurturing of relationships and individual autonomy. Our work identified additional factors that may be influenced by general practice – continuity of care, sensitivity to the expertise of care home staff and a willingness to dedicate time to patients. How to foster and sustain these attitudes and values, in the dynamic and pressurised environment of English primary care, is an important concern. Implementation research Our findings provide support for the changes being introduced in the EHCH Framework. However, they also point to a need for a greater understanding of how to introduce change into the complex setting of primary care for care homes. Unintended consequences of new initiatives, and a failure to take into account the human relationships involved are important but often overlooked challenges. Innovation that is taken up enthusiastically by a subset of the community may flounder when it is rolled out to other practices and care homes, with different interests and challenges. General principles to guide implementation already exist. This study suggests that there may be a place for the evidence to be synthesised to produce a practical toolkit for health and care home organisations embarking on service redesign. Greater use of ethnographic methods General practices and care homes are small, autonomous organisations, with ways of working that have often developed over years. Both are businesses, dependent on securing the trust of their current and future clients. For all of these reasons and others, insights into the way in which these organisations work, may be particularly difficult to obtain with standard qualitative interviews. Staff may be reluctant to reveal perceived flaws in their work or organisation, or keen to present their colleagues in a good light. Ethnographic methods offer an approach that allows the researcher to observe what is happening day to day and develop a deep and nuanced understanding of the workings of complex and impenetrable organisations. Greater acceptance of the value of ethnography by research ethics and research governance committees is needed to facilitate more widespread use of the approach in primary care and care homes. A whole systems approach The data presented in this study emphasises the needs for a whole systems approach to evaluative research in primary care and care homes. A change in one aspect of working leads to planned and unexpected consequences in other parts of the system. The impact on increased primary care contacts on hospital and primary care costs is an important topic for further study, to evaluate impact across the system. Further detailed work on the cost of changing ways of working in primary care may be helpful to support arguments for change, and appropriate allocation of resources. Care pathways This study identified a lack of guidance or care pathways specific to care home residents, either for general practice or care home use. Whether the complexities of older adult care can be safely incorporated into general guidance is an important question. However, our findings suggest that this is a void that will be filled by measures from secondary care (such as the national early warning score). Researchers could usefully address the question of whether care pathways or best practice guidance would improve the outcomes and efficiency of resident care, and be feasible to develop. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 14/196/05) and is published in full in Health and Social Care Delivery Research; Vol. 13, No. 11. See the NIHR Funding and Awards website for further award information.